2020
DOI: 10.1038/s41598-020-57713-4
|View full text |Cite
|
Sign up to set email alerts
|

Design Strategy to Create Antibody Mimetics Harbouring Immobilised Complementarity Determining Region Peptides for Practical Use

Abstract: 300 s. The dissociation of the interaction was subsequently measured for 300 s. Systematic baseline drift correction was done by subtracting the shift recorded for sensors loaded with ligand but incubated without analyte. Data analysis and curve fitting were done using Octet software version 11.0. Experimental data were fitted with the binding equations available for a 1:1 interaction with local fitting and the mean ± standard error of the mean (SEM) values of k on and k off were calculated from the data of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…The HBP of HBP-FLAP must be exposed on the surface of the molecule because the GA site was selected because it is a solvent exposed loop in the FN3 structure. 18 Therefore, the proteolysis resistance of the HBP in HBP-FLAP is not because of reduced protease access to the target sequence but is likely due to its immobilized structure, which restricts protease activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The HBP of HBP-FLAP must be exposed on the surface of the molecule because the GA site was selected because it is a solvent exposed loop in the FN3 structure. 18 Therefore, the proteolysis resistance of the HBP in HBP-FLAP is not because of reduced protease access to the target sequence but is likely due to its immobilized structure, which restricts protease activity.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 In addition, previous calculations revealed that residues 51-56 of FN3 are a gra acceptor (GA) site in which the structure of graed hexapeptides can be immobilized. 18 FN3 has been used for the development of affinity proteins targeting various antigens by protein engineering, 23,24 some of which have entered clinical trials, 25 suggesting that FN3 is a promising scaffold for creating HBP-FLAP. The HBPs were rst isolated from a phage-displayed peptide library ( Fig.…”
Section: Strategy For Creating Hbp-flapmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with previous findings that light chain CDRs generally play a more secondary or supporting role in target binding, such as stabilization of other CDRs. [15][16][17] Finally, we calculated the RMSD values of the HER2-binding residues between the three models and the antigen-free and antigen-bound structures of trastuzumab Fab. The rank 1 model yielded RMSD values of 1.64 and 1.86 Å to the antigen-free and antigen-bound structures, respectively; rank 2, 1.73 and 2.00 Å; and rank 3, 1.74 and 2.10 Å.…”
Section: Evaluation Of D-flap Binding To Her2mentioning
confidence: 99%
“…[11,12] An alternative approach is to use mAb-derived CDRs. Since antibody paratopes are usually formed by a combination of dominant and ancillary CDRs [15][16][17] that bind to linear or planar epitopes, [14] optimal paratope reconstitution is difficult with a single CDR graft onto a small protein scaffold. However, grafting multiple CDR peptides onto a small protein scaffold is challenging.…”
Section: Introductionmentioning
confidence: 99%